Spiritual Care Visualized - John S. Lunn (Health for All Nations, 2019)
Years ago, the author was asked by a prominent palliative care leader if spiritual care could be conveyed in a ladder format as pain management had been by the World Health Organization (WHO). Many practitioners think about spiritual care as a way to identify and address spiritual distress. It is a way to address spiritual distress and so much more. In this article, an attempt has been made to depict spiritual care visually. Spiritual care providers and others will tell you that along with spiritual distress, there is also a powerful resource that spirituality provides. The spiritual care ladder endeavors to show both aspects, along with their relationship to one another and their inter-connectedness. This is not a resource for assessing spirituality; it is meant to help people better understand it and to visualize it so that the tools will be more helpful. Several valuable tools have been included in this article for the assessment of spirituality and faith components of a person's life.